PRODUKSI ANTIBODI POLIKLONAL HASIL INDUKSI ISOLAT PROTEIN NON KINASE DARI MEMBRAN SPERMATOZOA MANUSIA - Lestari, Umie; Purnomo, Basuki B (Indonesian Urological Association, 2008)
Objective: The aim of this research is to get the profile of human sperms membrane protein based on identification for molecular weight, concentration protein, phosphorylation activity, and ability to raise enough antibodies. Material and methods: There are three phases in this research, first, isolation protein of human sperms membrane with using lysis buffer containing Tween-20, second, determination of molecular weight, phosphorylation activity, and protein concentration, and third, antibody production. Molecular weight of protein membrane was detected by SDS-PAGE, confirmation of protein concentration measured Biuret method, kinase activity measured using spectrophometry at its optimum condition, and then production of antibody that corfirmed by ELISA technique. Results: Human sperms contain the protein with molecular weight of 201, 163, 116, 97, 72, 56, 48, 32, 27, 20, and 17kDa. The highest phosphorylation activity was found on protein with molecular weight of 20 kDa is 30.197x 10-3 unit, while the lowest phosphorylation activity is 28.976x10-3 unit was shown on protein with 116 kDa of molecular weight and then this protein can induce production of antibody. Biuret method show the protein concentration from protein with molecular weight 116 kDa is 410 ug/mL. Conclusion: The protein that has molecular weight of 116 kDa can be used as immunocontraception agent because phosphorylation activity has lower, good concentration, and could induce the production of antibody.